Understanding farm typology for targeting agricultural development in mixed crop-livestock farming systems of Ethiopia - Awoke Eshetae, Meron; Abera, Wuletawu; Tamene, Lulseged D.; Mulatu, Kalkidan; Tesfaye, Abonesh (Elsevier, 2024)
Capturing the heterogeneity of farming systems through farm typology is essential for targeting agricultural interventions in any mixed crop-livestock farming system. Therefore, this study aims to construct a farm typology for the Doyogena and Basona districts of Southern and Northern Ethiopia, respectively. A combination of principal component analysis (PCA) and hierarchical clustering (HC) was used to develop a generalized and domain-specific farm typology in the study areas using farm household survey data collected from 503 respondents. A generalized farm typology was constructed considering all the dataset variables whereas the domain-specific farm typology was developed once all the data variables had been categorized into three groups: variables that describe i) the resource endowment, ii) technologies used, and iii) food and nutrition characteristics of the farm. The farm types identified from the domain-specific farm typologies were merged to develop comprehensive, representative, and meaningful farm types. In both districts, the results of the generalized farm typology are more generic, and are not able to fully capture the diversity of farmers’ resource endowment and food and nutrition security status. Compared to the generalized farm typology, the domain-specific farm typology is more useful for targeting tailored agricultural development interventions. The merged typology results show that a combination of medium resource endowment with medium income, medium technology, and low food and nutrition security farm type (34%) is the dominant farm type in the study areas followed by a farm type combining low resource endowment with low income, high technology and marginal food and nutrition secure (21%). The findings of this study provide several insights into targeting and scaling domain-specific agricultural development interventions that can be applicable for sustainable intensification of mixed farming systems. For example, growing multiple crops in crop rotations and as intercrops; implementing conservation tillage, and introducing improved seed varieties, and livestock breeds offer possible pathways for sustainable agricultural intensification for medium resource endowment, medium technology, and low food and nutrition security farm types.